Stray Light Absorption Film
By using polarizing films with macro structure and nanostructure on the sensor packaging, the problem of unnecessary light interference is solved, and the effects of low reflectivity and high signal-to-noise ratio are achieved.
Patent Information
- Application Number
- JP2020537226
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-01-05
- Filing Date
- 2019-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2039-01-03
AI Technical Summary
In the prior art, a straight or unwanted light may cause a decrease in deviation data or signal-to-noise ratio on the sensor packaging, especially in automobiles or outdoor environments where strong light sources such as headlights can cause interference.
A polarizing film containing a black substrate material, a macrostructure and a nanostructure is used. The average maximum diameter of the macrostructure is between 0.5 and 125 microns, while the average maximum diameter of the nanostructure is less than half of the macrostructure. This film effectively absorbs and scatters unnecessary light through a combination of macrostructure and nanostructure.
The total reflectivity and gloss reflectivity are significantly reduced, ensuring low reflectivity in the range of 350-1200 nm, reducing interference to the sensor signal, thereby improving the signal-to-noise ratio.
Smart Images

Figure 0007660372000008 
Figure 0007660372000009 
Figure 0007660372000010
Abstract
Description
[Technical field]
[0001] Stray or unwanted light can introduce aberrant data into the sensor package or can result in poor signal-to-noise ratio for the measurement data. When using films, light can be absorbed in the optical cavity. Summary of the Invention
[0002] In one aspect, the present disclosure relates to a stray light absorbing film. Specifically, the stray light absorbing film includes a black substrate, a first set of microstructures disposed on a major surface of the substrate, and a second set of microstructures disposed on the major surface of the substrate. The first set of microstructures are characterized by an average largest diameter between 0.5 and 125 μm. The second set of microstructures are characterized by an average largest diameter that is less than ½ of the average largest diameter of the first set of microstructures.
[0003] In another aspect, the present disclosure relates to a stray light absorbing film. Specifically, the stray light absorbing film includes a black substrate, a set of irregular faceted microstructures disposed on a major surface of the substrate, and a set of nanostructures disposed on the set of irregular faceted microstructures. The nanostructures are holes in the set of irregular faceted microstructures. None of the nanostructures are larger than the average maximum diameter of the set of irregular faceted microstructures.
[0004] In yet another aspect, the present disclosure relates to a stray light absorbing film comprising a polymeric substrate having a structured surface, the stray light absorbing film having a total reflectance of less than 5% at 8° incidence from 350-1200 nm.
[0005] In another aspect, the present disclosure relates to a stray light absorbing film comprising a polymeric substrate having a structured surface, the stray light absorbing film having a specular reflectance of less than 1% at 8° incidence from 350-1200 nm.
[0006] In yet another aspect, the present disclosure relates to a stray light absorbing film comprising a polymeric substrate having a structured surface, the stray light absorbing film having a CIE-Y photopic reflectance in an integrating sphere of less than 5%.
[0007] In another aspect, the present disclosure relates to a stray light absorbing film comprising a polymeric substrate having a structured surface. The stray light absorbing film has an 85 degree gloss of less than 5 gloss units.
[0008] In yet another aspect, the present disclosure relates to a stray light absorbing film comprising a polymeric substrate having a structured surface. The stray light absorbing film has a bright reflectance of less than 4% at a BDRF cutoff of 0.01. [Brief description of the drawings]
[0009] [Figure 1] 1 shows a BRDF scattering map and cross section plot for Comparative Sample A. [Diagram 2] 13 shows a BRDF scattering map and cross section plot for Comparative Sample B. [Diagram 3] 13 shows a BRDF scattering map and cross section plot for sample C. [Figure 4] 13 shows a BRDF scattering map and cross section plot for sample D. [Diagram 5] 13 shows a BRDF scattering map and cross section plot for sample E. [Figure 6] 1 shows the total reflectance at 8° incidence for comparative samples A and B, and samples C, D, and E for wavelengths from 350 nm to 1200 nm. [Figure 7]1 shows the specular reflectance at 8° incidence for comparative samples A and B, and samples C, D, and E for wavelengths from 350 nm to 1200 nm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Sensors and sensor packages are typically designed to detect light within a limited angle or solid angle range. To maintain an acceptably high signal-to-noise ratio, it is necessary that as little light as possible outside the range of interest reach the sensor. Unfortunately, especially in automotive or outdoor environments, there is a lot of glare, reflections, and potentially disturbing light from headlights and other strong light sources. The films described herein can help reduce noise from light trapped in the sensor cavity or from high angle incident light.
[0011] The films described herein have both macrostructured and nanostructured surface profiles. In some embodiments, the macrostructures can be formed from a microreplication process. In some embodiments, the macrostructured surface profile can include features having an average maximum diameter of 0.5 μm to 125 μm. In some embodiments, the macrostructured surface profile can include features having an average maximum diameter of 0.5 μm to 15 μm. In some embodiments, the macrostructured surface profile can include grooves or ridges. In some embodiments, the macrostructured surface profile can include a series of linear prisms. In some embodiments, the macrostructured surface includes random microstructures, pseudo-random microstructures, discrete microstructures, canted microstructures, or any combination thereof. Although macrostructured surfaces are macroscopic to nanostructured surface profiles, they can be formed from a process conventionally known as microreplication, and thus may also be referred to as microstructures.
[0012] The macrostructures of the structured surface profile of the present invention are integral, i.e., the macrostructures are formed into the microstructures, for example, via a molding process, and no additional material is added to the surface to allow or accelerate the formation of the macrostructures. In some embodiments, the "randomness" of the distribution of the macrostructures is in a repeating pattern. This is due to the configuration of the mold used to provide such a macrostructured surface and its repeated use. The macrostructured surface profile can be formed using a suitable high-definition process, for example, a continuous cast and cure process, or a batch process.
[0013] A suitable microreplicatable resin carried on a substrate is contacted with a tool or mold having the inverse of the desired features. The resin is then hardened, crosslinked, or cured, for example by exposure to ultraviolet light, and removed to form the macrostructured surface profile. To form one embodiment of the macrostructured surface, the microstructured roll is subjected to an electroplating process.
[0014] A base or substrate may be prepared to serve as a substrate onto which a metal layer may be electroplated. The substrate may take one of many forms, such as a sheet, plate, or cylinder. A circular cylinder is advantageous in that it may be used in the manufacture of continuous roll goods. The substrate is typically made of metal, with exemplary metals including nickel, copper, and brass. However, other metals may be used. The substrate has an exposed surface (the "base surface") on which the electro-deposited layer is formed in a subsequent step. The base surface may be smooth, flat, or substantially flat. The outer curved surface of a polished smooth cylinder may be considered to be substantially flat, especially when considering a small localized area in the vicinity of a given point on the surface of the cylinder.
[0015] A first layer of metal is then formed on the base surface of the substrate using a first electroplating process. Prior to this step, the base surface of the substrate may be primed or otherwise treated to enhance adhesion. The metal may be substantially the same as the metal that constitutes the base surface. For example, if the base surface comprises copper, the formed first electroplated layer may also be made of copper. To form the first layer of metal, the first electroplating process uses a first electroplating solution. The composition of the first electroplating solution, e.g., the type of metal salt used in the solution, as well as other process parameters such as current density, plating time, and substrate speed, are selected to form the first electroplated layer not smooth and flat, but instead to have a first major surface characterized by structured, irregular, flat-faceted features. The size and density of the irregular features are determined by the current density, plating time, and substrate speed, while the type of metal salt used in the first electroplating solution determines the geometry of the features. Further teachings in this regard can be found in U.S. Patent Application Publication No. 2010 / 0302479 (Aronson et al.). By performing a first plating process, the first major surface of the first electroplated layer has a first average roughness that is greater than the base average roughness of the substrate.
[0016] The shape and size of the macrostructures will vary depending on the type of metal being electroplated onto the roll former. The shape and size of the macrostructures will be the inverse of the shape and size of the metal structure being plated onto the roll. Such shapes include pores, semi-hemispheres, "zig-zag" valleys, "craters", and shapes replicating the surface of a cauliflower. The macrostructures may overlap, nest within one another, or be separate from one another. The size, i.e., maximum diameter, of the macrostructures may range from about 0.5 micrometers (μm) to about 125 μm at the maximum diameter. A typical range is 0.5 to 15 μm. The area of the macrostructures may range from about 0.01 to about 1100 μm squared. The depth may range from about 0.2 to about 20 μm. The macrostructured surface may have an average surface slope of 10 to 20 degrees, 20 to 30 degrees, 35 to 55 degrees, or 40 to 50 degrees.
[0017] The nanostructures of the nanostructured surface may be any shape and size. In some embodiments, the nanostructures may be pores formed in the surface. In some embodiments, these pores may have an average maximum diameter that is less than half the average maximum diameter of the macrostructures. In some embodiments, the average maximum diameter of the nanostructures is less than 1 / 5, or even less than 1 / 10, of the average maximum diameter of the macrostructures. In some embodiments, the nanostructures have an average maximum diameter that is less than 100 nm, less than 50 nm, less than 20 nm, or even less than 10 nm. In some embodiments, none of the nanostructures is larger than the average maximum diameter of the macrostructures.
[0018] The nanostructured surface of the film described herein can be formed from a reactive ion etching process on a discontinuously deposited masking layer. For example, in one embodiment, a thin random discontinuous masking layer is applied to the main surface of the macrostructured film by plasma chemical vapor deposition to form the nanostructured surface. The random discontinuous masking layer is a reaction product of plasma chemical vapor deposition using a reactive gas that includes a compound selected from an organosilicon compound, a metal alkyl, a metal isopropoxide, a metal acetylacetonate, and a metal halide. Typically, the organosilicon compound can include tetramethylsilane, trimethylsilane, hexamethyldisiloxane, tetraethylorthosilicate, or polyhedral oligomeric silsesquioxane. Useful metal alkyls can include trimethylaluminum, tributylaluminum, tributyltin, or tetramethylgallium. Useful metal isopropoxides can include titanium isopropoxide, or zirconium isopropoxide. Useful metal acetylacetonates can include platinum acetylacetonate, or copper acetylacetonate. Useful metal halides can include titanium tetrachloride, or silicon tetrachloride.
[0019] Plasma chemical vapor deposition (or plasma enhanced chemical vapor deposition) is a process whereby a plasma is typically generated by a radio frequency discharge and is formed in the space between two electrodes when the space is filled with a reactive gas. Plasma chemical vapor deposition is performed under vacuum to reduce side reactions from undesired species present in the reaction chamber. The reactive gas typically deposits a thin solid film on the substrate. A random discontinuous masking layer is formed on the macrostructured film using plasma chemical vapor deposition. It has been found that certain chemical species form random discontinuous islands of material when the plasma is deposited on the substrate for a very short time. For example, in Example 1 of U.S. Pat. No. 8,634,146 (David et al.), the reactive gas was tetramethylsilane, the substrate was poly(methyl methacrylate), and plasma enhanced chemical vapor deposition was conducted at a pressure of about 10 mTorr, a plasma power of about 100-200 Watts, and a web speed of about 7 ft / min to about 9 ft / min (213 cm / min to 274 cm / min) to produce random, discontinuous islands of polymerized tetramethylsilane on the substrate.
[0020] Typically, when reactant gases derived from relatively small organic or organometallic compounds are plasma-enhanced chemical vapor deposition onto a prepared substrate, they initially form small islands of reacted material. Without being bound by theory, this effect is similar to a small amount of liquid, such as water, which is likely to initially bead on a surface with a different surface energy. In a similar manner, when a small amount of products produced by plasma-enhanced chemical vapor deposition are initially deposited onto a prepared substrate, they tend to initially clump together into small islands that are random and discontinuous patterns. In the provided method, the deposition is stopped before any coalescence occurs by adjusting the reaction conditions (web speed, plasma discharge energy, substrate exposure time, etc.). From this, the deposition masking layer is random and discontinuous. The individual islands typically have an average dimension of less than about 400 nm, less than about 200 nm, less than about 100 nm, less than about 50 nm, or even less than about 20 nm.
[0021] The provided method includes etching portions of the major surface that are not protected by the masking layer to form nanostructures on the macrostructured film. In some embodiments, the etching and deposition can be performed simultaneously as in U.S. Patent Application Publication No. 2017 / 0067150 (David et al.). These nanostructures may appear as holes with high aspect ratios. In some embodiments, these holes may have their longest dimension along a length direction, and the length direction may be within 10 degrees of the normal to the plane of the film. In some embodiments, the length direction may not be within 10 degrees of the normal to the plane of the film.
[0022] Typically, reactive ion etching is used for etching. In one embodiment, this can be done using a continuous roll-to-roll process called "cylindrical reactive ion etching" (cylindrical RIE). Cylindrical RIE utilizes a rotating cylindrical electrode to obtain anisotropically etched nanostructures on the surface of a substrate or article. In general, cylindrical RIE can be described as follows: A rotatable cylindrical electrode ("drum electrode") powered by radio frequency (RF) and a grounded counter electrode are provided inside a vacuum vessel. The counter electrode may comprise the vacuum vessel itself. An etchant gas is fed into the vacuum vessel and a plasma is ignited and maintained between the drum electrode and the grounded counter electrode.
[0023] The continuous substrate, including the random discontinuous mask layer, can then be wrapped around a drum and the substrate can be etched normal to the plane of the substrate or at an oblique angle relative to the normal to the plane of the substrate. The exposure time of the substrate can be controlled to obtain a predetermined etch depth of the resulting nanostructures. The process can be carried out at an operating pressure of about 10 mTorr. Cylindrical RIE is disclosed, for example, in International Application Publication No. US / 2009 / 069662 (David et al.).
[0024] The films described herein having both macrostructured and nanostructured surface profiles are formed using a light-absorbing substrate. In some embodiments, the light-absorbing substrate may be or include a polymeric material (e.g., polyethylene terephthalate, polycarbonate, poly(methyl methacrylate), polycarbonate, etc.) with a broadband absorber such as carbon black. In some embodiments, the absorber may be or include a wavelength-specific absorber, such as an absorber, dye, or pigment that absorbs near-infrared light. In some embodiments, the substrate may include a downconverter, such as a fluorescent material or quantum dot, that absorbs light at a specific wavelength and re-emits light at a longer wavelength, for example, absorbing light that may interfere with a sensor or sensor device and re-emits it at a wavelength that is not detectable.
[0025] The nanostructured surfaces described herein have been used for antireflective surfaces. Antireflective surfaces increase light coupling to the substrate and increase transmission by minimizing light lost to Fresnel reflections. For films described herein that are not transparent, the antireflection treatments are unusual. Surprisingly, these antireflective surfaces, in combination with the irregular faceted macrostructure, significantly reduce both the overall overall reflectance and the specular reflectance. This reduction in both overall reflectance and specular reflectance is significantly greater than can be achieved by simply applying an antireflective treatment to a flat absorbing substrate. For example, in some embodiments, films described herein having both macrostructured and nanostructured surface profiles can have a total reflectance of less than 5%, less than 4%, less than 3%, less than 2%, or even less than 1% at 8° incidence over the range of 350-1200 nm. Films described herein having both macrostructured and nanostructured surface profiles can have a specular reflectance of less than 2%, less than 1%, less than 0.5%, or even less than 0.3% at 8° incidence in the range of 350-1200 nm. Films described herein having both macrostructured and nanostructured surface profiles can have a CIE-Y average luminous reflectance in an integrating sphere of less than 5%, less than 4%, less than 3%, or even less than 2%. Films described herein having both macrostructured and nanostructured surface profiles can have an 85 degree gloss of less than 5 gloss units, less than 2 gloss units, or even less than 1 gloss unit. Films described herein having both macrostructured and nanostructured surface profiles can have a shiny reflectance of less than 3%, less than 2%, less than 1%, or even less than 0.5% at a BDRF cutoff of 0.06.Films described herein having both a macrostructured surface profile and a nanostructured surface profile can have a shiny surface reflectance of less than 3%, less than 2%, less than 1%, or even less than 0.5% at a BDRF cutoff of 0.03. Films described herein having both a macrostructured surface profile and a nanostructured surface profile can have a shiny surface reflectance of less than 4%, less than 2%, or even less than 1% at a BDRF cutoff of 0.01. Films described herein having both a macrostructured surface profile and a nanostructured surface profile can have a shiny surface reflectance of less than 4%, less than 2%, or even less than 1% at a BDRF cutoff of 0.005.
[0026] The films described herein can be used in applications such as the interior cavity of a head-up display (or another projection system) or inside a liquid crystal display (LCD) to prevent contrast loss from stray or stray light in these systems. In some embodiments, these films can be used in sensors such as LiDAR sensors for automotive applications or for any other application. In some embodiments, the films described herein can include an adhesive layer (formed as a tape) for attachment inside the optical cavity. The films described herein can be curved, corrugated, embossed, or otherwise three-dimensionally shaped. In some embodiments, these films can be shaped to conform to the inner shape of the cavity. The films described herein can be shaped by thermoforming, insert molding, or similar processes. In applications where the films described herein are exposed to ambient conditions and radiation such as sunlight, such films can be laminated or otherwise placed in thermal contact with a thermally conductive material or heat sink. EXAMPLES
[0027] Objects and advantages can be further illustrated by the following examples, but the particular materials and amounts thereof recited in these examples, as well as other conditions and details, should not be construed to unduly limit this disclosure.
[0028] Samples were prepared with the materials listed in Table 1.
[0029] [Table 1]
[0030] Comparative Sample A was a 175 μm thick Hostaphan BPV7D film having a width and length of about 20-25 centimeters and 25-30 centimeters, respectively. No microstructures or nanostructures were formed on any surface of Comparative Sample A.
[0031] Comparative sample B is a 175 μm thick Hostaphan BPV7D film having a width and length of about 20-25 cm and 25-30 cm, respectively, with a nanostructured surface on one film side. 3 Hexamethyldisiloxane flow rate of 750 cm3 / min 3 A nanostructured surface was formed on the discontinuous deposition masking layer from a reactive ion etching process with process settings including an oxygen flow rate of 1000 nm / min, a radio frequency power of 7500 watts, and a web translation speed of 76.2 cm / min. Comparative Sample B has a measured thickness of about 173 μm.
[0032] Sample C was a substrate film having a width and length of approximately 20-25 centimeters and 25-30 centimeters, respectively, with nanostructures and microstructures formed on one surface. The microstructures were formed on the film substrate surface with high definition using a tool formed from an electroplated microreplication tool with irregular flat facet features. This tool was used to create the microstructures by a cast and cure process as described in U.S. Pat. No. 5,1175,030. The substrate film was a 175 μm thick Hostaphan BPV7D film, and the resin used in the cast and cure process was a UV-curable acrylic filled with black pigment. The UV-curable acrylic resin composition used for this sample is listed in Table 2. 10 cm 3 Hexamethyldisiloxane flow rate of 750 cm3 / min 3 A nanostructured surface was formed on the microstructured surface from a reactive ion etching process over the discontinuous deposition masking layer with process settings including an oxygen flow rate of 1000 μm / min, a radio frequency power of 7500 watts, and a web translation speed of 76.2 cm / min. Sample C has a measured thickness of 190-200 μm.
[0033] Sample D is a substrate film having a width and length of about 20-25 centimeters and 25-30 centimeters, respectively, with microstructures formed on two major surfaces of the substrate film and nanostructures formed on one major surface. The microstructures were formed on the two major surfaces of the film substrate with high definition on each surface using a tool formed from an electroplating high definition tool with irregular flat facet features. This tool was used to create the microstructures by a cast and cure process as described in U.S. Pat. No. 5,1175,030. The substrate film was a 175 μm thick Hostaphan BPV7D film, and the resin used in the cast and cure process was a UV curable acrylic resin filled with black pigment. The UV curable acrylic resin composition used for this sample is listed in Table 2. 10 cm 3Hexamethyldisiloxane flow rate of 750 cm3 / min 3 A nanostructured surface was formed on the microstructured surface from a reactive ion etching process over the discontinuous deposition masking layer with process settings including an oxygen flow rate of 1000 μm / min, a radio frequency power of 7500 watts, and a web translation speed of 76.2 cm / min. Sample D has a measured thickness of 205-210 μm.
[0034] Sample E is a substrate film having a width and length of about 20-25 cm and 25-30 cm, respectively, with microstructures formed on two major surfaces of the substrate film and nanostructures formed on one major surface. The microstructures were formed on the two major surfaces of the film substrate by fine definition of each surface using a tool formed from an electroplating fine definition tool with irregular flat facet features. This tool was used to create the microstructures by a cast and cure process as described in U.S. Pat. No. 5,1175,030. The substrate film was a 175 μm thick Hostaphan BPV7D film, and the resin used in the cast and cure process was a UV curable acrylic resin filled with black pigment. The UV curable acrylic resin composition used for this sample is listed in Table 2. Fine definition of the microstructures on each major surface was performed three times. 10 cm 3 Hexamethyldisiloxane flow rate of 750 cm3 / min 3 A nanostructured surface was formed on the microstructured surface from a reactive ion etching process over the discontinuous deposition masking layer with process settings including an oxygen flow rate of 1000 μm / min, a radio frequency power of 7,500 watts, and a web translation speed of 76.2 cm / min. Sample E has a measured thickness of 240-250 μm.
[0035] [Table 2]
[0036] Example 1. Scatterometry test The bidirectional reflectance distribution function (BRDF) was measured for each sample at angles of incidence of 0°, 15°, 30°, 45°, 60°, and 75° with a Radiant Imaging IS-SA Imaging Sphere (Radiant Vision Systems, formerly known as Radiant Imaging, Redmond, WA, USA). BRDF is a term known in the art and generally relates to the ratio of scattered luminance to incident illuminance for a given incidence direction and a given scattering direction. The photopic BRDF corresponds to the CIE-Y BRDF measured with this instrument. This instrument gives the CIE-Y value for an E illuminant.
[0037] Bright surface reflectance provides a measure of effective reflectance for applications where stray light with high amplitude peaks is undesirable. An ideal stray light sample is a surface that minimizes the effect of stray light for all geometries and is a Lambertian surface with low total reflectance. In some cases, the ideal stray light sample is a black surface. Bright surface reflectance is the reflectance obtained by integrating the measured BRDF over the area above the BRDF cutoff value. The formula for bright surface reflectance is presented below:
number
number
[0038] q is the angle between the scattering direction and the sample normal, and φ is the azimuthal angle with respect to the x-axis (horizontal axis of the IS-SA).
[0039] A is (θ X ,θ Y ) space, θ≦82°, excluding the blind spot of the IS-SA in the direction of the incident light. Note that the integral is X and θ YThe angle is measured in radians.
number
[0040] When the BRDF cutoff is equal to zero, the measured specular reflectance is approximately equal to the measured total reflectance. The BRDF cutoffs were set at 0.005, 0.01, 0.03, and 0.06. A perfect Lambertian reflector with 100% total reflectance would have a constant BRDF of 0.318. These BRDF cutoff values are therefore approximately 5-60 times lower and represent reasonably low BRDFs. The average specular reflectance was calculated as the specular reflectance averaged over the incidence angles used to measure the BRDF. The average total reflectance, average specular reflectance, and average specular reflectance were all calculated from the BRDF data and reported for all samples in Table 3. The average for each case was taken over incidence angles of 0°, 15°, 30°, 45°, 60°, and 75°. The average specular reflectance was reported for the four BRDF cutoffs.
[0041] [Table 3]
[0042] The results show that Comparative Sample A provides the highest average total reflectance and average shiny surface reflectance, which is undesirable for aiding in reducing stray light when used in LiDAR sensor applications. The results further show that Comparative Sample B provides high average total reflectance and average shiny surface reflectance, which reduces the average shiny surface reflectance relative to Comparative Sample A, but is still undesirable when used in LiDAR sensor applications. Results from Samples C, D, and E show that the reduction in average shiny surface reflectance relative to Comparative Sample A is over 9 times and 200 times as great. Results from Samples C, D, and E show that the reduction in average shiny surface reflectance relative to Comparative Sample B is over 4 times and 80 times as great.
[0043] For all samples analyzed, we exclude the BRDF in the direction of the incident light. By fabricating special optical configurations, it is possible to measure the BRDF in this direction, but typical commercial scatterometers, including the IS-SA Imaging Sphere, do not have this capability. For the 0 degree case, this results in specular exclusion. No hole filling was used to obtain interpolated data in the direction of the incident light.
[0044] BRDF data was extracted using a step size of 0.25 degrees and an integration diameter. The intrinsic resolution of the IS-SA Imaging Sphere at the settings used is approximately 1.5 degrees. Cross-section plots were made with a resolution of approximately 2 degrees. A BRDF scattering map and a cross-section plot of the BRDF scattering map were made, which show the scattering distribution of the reflected light.
[0045] Figure 1 shows the BRDF scattering map and cross section plot for Comparative Sample A at an incidence angle of 75°. Note that Comparative Sample A has a low BRDF, except for a peak magnitude of over 400 at about 75°.
[0046] Figure 2 shows the BRDF scattering map and cross-section plot for Comparative Sample B, where the angle of incidence is 75° on the plane of the nanostructured surface. Note that Comparative Sample B also has a low BRDF, except for a peak magnitude of over 100 at about 75°, just below the quarter-wave scattering function.
[0047] 3 shows the BRDF scattering map and cross-section plot for Sample C, where the angle of incidence is 75° on the surface with the nanostructured surface, and Sample C has a peak BRDF scattering value of just over 0.32 between 80° and 90°.
[0048] 4 shows the BRDF scattering map and cross section plot for Sample D, where the angle of incidence is 75° on the plane with the nanostructured surface, and Sample D has a peak BRDF scattering value of just over 0.42 between 80° and 90°.
[0049] 5 shows the BRDF scattering map and cross section plot for Sample E, where the angle of incidence is 75° on the surface with the nanostructured surface. Sample E has a peak BRDF scattering value of just over 0.14 between 80° and 90°.
[0050] Example 2. Specular gloss test The specular gloss of Comparative Samples A and B, and Samples C, D, and E was measured using ASTM D 523-14-Standard Test Method for Specular Gloss. The instrument used to collect 85 degree gloss readings was a BYK Tri-Gloss Meter Model 4520 available from BYK-Gardner (USA). The instrument was calibrated and run according to the instrument instructions in the instrument brochure, and measurements were collected. At least three values were collected for the examples according to the instructions in the ASTM D523-14 Standard Test Method. The 85 degree gloss was chosen compared to 20 degrees and 60 degrees because the higher 85 degree is considered the actual angle that encompasses the practicality of Samples C, D, and E. Table 4 lists the 85 degree gloss averaged over five readings per sample for Comparative Samples A and B, and Samples C, D, and E. The gloss rating as measured by this test method is obtained by comparing the specular reflectance from the test specimen to the specular reflectance from a black glass standard, which in this case measured 99.8 gloss units.
[0051] [Table 4]
[0052] Example 3. UV-Vis-NIR spectroscopy The ultraviolet to near infrared spectra were measured for each of the samples using a Lambda 1050 UV-Vis-NIR spectrophotometer (Perkin Elmer Life Sciences, Downers Grove, IL, USA) with a PELA-1002 integrating sphere attachment with a slit width of 5 nm. The incidence angle of the light source for this test was 8° relative to the normal to the sample surface. The data were corrected against a white PTFE reflectance standard. A single total reflectance spectrum and a single diffuse reflectance spectrum were obtained for each sample. A specular reflectance spectrum was obtained for each sample by subtracting the diffuse reflectance spectrum from the total reflectance spectrum.
[0053] FIG. 6 shows the total reflectance of comparative samples A and B, and samples C, D, and E for wavelengths from 350 nm to 1200 nm.
[0054] FIG. 7 shows the specular reflectance of comparative samples A and B, and samples C, D, and E for wavelengths from 350 nm to 1200 nm.
[0055] The total reflectance spectrum is less than 1% for Samples C, D, and E for wavelengths ranging from 350 nm to 1200 nm. The specular reflectance is indistinguishable from zero for Samples C, D, and E. Comparative Sample A has a specular reflectance spectrum over a 5% area. Comparative Sample B has a specular reflectance spectrum over a 1% area. In the following, exemplary embodiments are presented. [1] A stray light absorbing film, A black substrate; a first set of microstructures disposed on a major surface of the substrate; a second set of microstructures disposed on the major surface of the substrate; Including, the first set of microstructures is characterized by an average maximum diameter of 0.5 to 125 μm; a stray light absorbing film, wherein said second set of microstructures is characterized by an average maximum diameter that is less than 1 / 2 of said average maximum diameter of said first set of microstructures. [2] 2. The stray light absorbing film of [1], wherein the average maximum diameter of the second set of microstructures is less than 1 / 5 of the average maximum diameter of the first set of microstructures. [3] 2. The stray light absorbing film of [1], wherein the average maximum diameter of the second set of microstructures is less than 1 / 10 of the average maximum diameter of the first set of microstructures. [4] 2. The stray light absorbing film of [1], wherein the average maximum diameter of the second set of microstructures is less than 100 nm. [5] 2. The stray light absorbing film of [1], wherein each microstructure in the second set of microstructures is a hole having a longest dimension along a length direction, the average of said length direction being within 10 degrees of a normal to a plane of the substrate. [6] 2. The stray light absorbing film of [1], wherein each microstructure in the second set of microstructures is a hole having a longest dimension along a length direction, the average of said length direction being not within 10 degrees of a normal to a plane of the substrate. [7] The stray light absorbing film according to [1], wherein the substrate comprises polyethylene terephthalate. [8] The stray light absorbing film according to [1], wherein the substrate comprises poly(methyl methacrylate). [9] The stray light absorbing film according to [1], wherein the substrate comprises polycarbonate.
[10] The stray light absorbing film according to [1], wherein the substrate contains carbon black.
[11] The stray light absorbing film of [1], wherein the substrate further comprises a third set of microstructures disposed on a second major surface of the substrate opposite the first major surface.
[12] A stray light absorbing film, A black substrate; a set of irregular faceted microstructures disposed on a major surface of the substrate; a set of nanostructures disposed on the set of irregular faceted microstructures, the nanostructures being holes in the set of irregular faceted microstructures; A stray light absorbing film, wherein none of said nanostructures is larger than the average maximum diameter of said set of irregular faceted microstructures.
[13] 13. The stray light absorbing film of
[12] , wherein each nanostructured pore has a longest dimension along a length direction, the average of said length direction being within 10 degrees of a normal to the plane of the substrate.
[14] 13. The stray light absorbing film of
[12] , wherein each nanostructured pore has a longest dimension along a length direction, the average of said length direction being not within 10 degrees of a normal to a plane of the substrate.
[15] 1. A stray light absorbing film comprising a polymeric substrate having a structured major surface, the stray light absorbing film having a total reflectance of less than 5% at 8° incidence from 350-1200 nm.
[16] The stray light absorbing film according to
[15] , wherein the total reflectance at an incident angle of 8° at 350 to 1200 nm is less than 2%.
[17] The stray light absorbing film according to
[15] , wherein the total reflectance at an incident angle of 8° at 350 to 1200 nm is less than 1%.
[18] 1. A stray light absorbing film comprising a polymeric substrate having a structured major surface, the stray light absorbing film having a specular reflectance of less than 1% at 8° incidence from 350-1200 nm.
[19] The stray light absorbing film according to
[17] , wherein the regular reflectance at an incident angle of 8° at 350 to 1200 nm is less than 0.3%.
[20] 1. A stray light absorbing film comprising a polymeric substrate having a structured major surface, the stray light absorbing film having a CIE-Y average luminous reflectance in an integrating sphere of less than 5%.
[21] The stray light absorbing film according to
[20] , wherein the CIE-Y average luminous reflectance is less than 2%.
[22] A stray light absorbing film comprising a polymeric substrate having a structured major surface, the stray light absorbing film having an 85 degree gloss of less than 5 gloss units.
[23] The stray light absorbing film according to
[22] , wherein the 85 degree gloss is less than 2 gloss units.
[24] A stray light absorbing film comprising a polymeric substrate having a structured major surface, the stray light absorbing film having a bright surface reflectance of less than 4% at a BDRF cutoff of 0.01.
[25] The stray light absorbing film according to
[24] , wherein the bright surface reflectance is less than 1%.
[26] The stray light absorbing film according to any one of [1] to
[25] , which is curved.
[27] The stray light-absorbing film according to any one of [1] to
[26] , which is in thermal contact with a thermally conductive layer.
[28] The stray light-absorbing film according to any one of [1] to
[27] , further comprising an adhesive layer.
[29]
[28] An optical cavity comprising a stray light absorbing film according to
[28] .
[30] A sensor module comprising the stray light absorbing film according to any one of [1] to
[28] .
[31]
[30] A vehicle comprising the sensor module according to the present invention.
[32] A liquid crystal display device comprising the stray light absorbing film according to any one of [1] to
[28] .
[33] A head-up display device comprising the stray light absorbing film according to any one of [1] to
[28] .
Claims
1. A stray light absorbing film, A black substrate; a first set of microstructures disposed on a major surface of the substrate; a second set of microstructures formed on the major surface of the substrate and on the first set of microstructures by reactive ion etching over a random discontinuous masking layer; Including, the first set of microstructures is characterized by an average maximum diameter of 0.5 to 125 μm; the second set of microstructures is characterized by an average maximum diameter that is less than half the average maximum diameter of the first set of microstructures; A stray light absorbing film having a total reflectance of less than 1% at 8 degrees incidence over the range of 350-1200 nm and a specular reflectance of less than 0.3% at 8 degrees incidence over the range of 350-1200 nm.
2. 2. The stray light absorbing film of claim 1 , wherein said average maximum diameter of said second set of microstructures is less than 1 / 5 of said average maximum diameter of said first set of microstructures.
3. 2. The stray light absorbing film of claim 1 , wherein said average maximum diameter of said second set of microstructures is less than 1 / 10 of said average maximum diameter of said first set of microstructures.
4. 2. The stray light absorbing film of claim 1 , wherein said average maximum diameter of said second set of microstructures is less than 100 nm.
5. 2. The stray light absorbing film of claim 1 , wherein each microstructure in the second set of microstructures is a hole having a longest dimension along a length direction, the average of said length direction being within 10 degrees of a normal to a plane of the substrate.
6. 2. The stray light absorbing film of claim 1 , wherein each microstructure in the second set of microstructures is a hole having a longest dimension along a length direction, the average of said length direction being not within 10 degrees of a normal to a plane of the substrate.
7. 10. The stray light absorbing film of claim 1 wherein the substrate comprises polyethylene terephthalate.
8. 10. The stray light absorbing film of claim 1 wherein the substrate comprises poly(methyl methacrylate).
9. The stray light absorbing film of claim 1 wherein the substrate comprises polycarbonate.
10. 10. The stray light absorbing film of claim 1 wherein the substrate comprises carbon black.
11. 10. The stray light absorbing film of claim 1 , wherein said substrate further comprises a third set of microstructures disposed on a second major surface of said substrate opposite said major surface.
12. A stray light absorbing film, A black substrate; a set of irregular faceted microstructures disposed on a major surface of the substrate; a set of nanostructures formed on the set of irregular faceted microstructures by reactive ion etching over a random discontinuous masking layer, the nanostructures being holes in the set of irregular faceted microstructures; none of said nanostructures has a maximum diameter greater than the average maximum diameter of the set of said irregular faceted microstructures; A stray light absorbing film having a total reflectance of less than 1% at 8 degrees incidence over the range of 350-1200 nm and a specular reflectance of less than 0.3% at 8 degrees incidence over the range of 350-1200 nm.
13. 13. The stray light absorbing film of claim 12 wherein each nanostructured pore has its longest dimension along a length direction, the average of said length direction being within 10 degrees of normal to the plane of the substrate.
14. 13. The stray light absorbing film of claim 12 wherein each nanostructured hole has its longest dimension along a length direction, the average of said length direction being not within 10 degrees of a normal to a plane of the substrate.
15. A sensor module comprising the stray light absorbing film according to any one of claims 1 to 14.
Citation Information
Patent Citations
Curable resin film and method of manufacturing the same
JP2010175653A
Antireflection member and method for manufacturing the same
JP2017161590A
Laminated transfer film forming an antireflection structure
JP2017508640A
Optical article
US20100302479A1
Method of making a nanostructure and nanostructured articles
US20170067150A1